Ayn Rand versus Adam Smith. - White, Robert (Journal of Ayn Rand Studies (Journal of Ayn Rand Studies Foundation))
This article compares Ayn Rand's trader principle with Adam Smith's invisible hand principle. Rand's defense of laissez-faire capitalism is often confused with Smith's defense of the market economy. White argues that Rand and Smith do not share the same ideas on the importance of self-interest or support the same sort of minimalist government, and that these are important and substantial differences between the two thinkers. He examines the antitrust case against Microsoft as one example of the importance of these differences.